The efficacy of alignment-based and alignment-free methods in reconstructing phylogenetic trees using complete mitochondrial DNA sequence / Elham Yousef Kalafi - Kalafi, Elham Yousef (2012)
Similarity searching tools are generally divided to two distinct groups: Alignment-based and alignment-free methods. There is no standard comparison between alignment-based and alignment-free methods` performance. In this project, I compared CLUSTALW, T-COFFEE and MUSCLE algorithms with four alignment-free methods, Kr, D2, D2z and MplusD to find out which of these methods are more efficient with respect to time and accuracy. In both alignment-based and alignment-free, results are represented by phylogenetic trees. Here, all phylogenetic trees are compared against the reference tree to determine how accurate the methods are. I found that alignment-based methods were the most accurate comparing to alignment-free methods. On the other hand, Kr and D2z gave approximately correct results with substantial gain in speed. I conclude that for inferring phylogenetic trees containing taxa that have diverged for a long time, alignment-based methods should be used. However if many closely related species are studied, then an alignment-free method should worth well.